A new species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from the Central Philippines - Osawa, Masayuki (Zootaxa, 2018)
A new species of porcelain crab, Polyonyx angustus n. sp., is described on the basis of material collected from Panglao Island, the Central Philippines. It is morphologically allied to P. boucheti Osawa, 2007, P. pilosibrachium Osawa, Naruse & Ng, 2018, and P. utinomii Miyake, 1943, but distinguished by the shape of the carapace and rostrum. Re-examination of the specimens from the Maldives previously referred to P. utinomii has showed that they belong to the new species instead. The present knowledge suggests that P. utinomii is distributed only in the Japanese main islands from central Honshu to Kyushu.